Schoolhouse rock! [videorecording (DVD)] (Disney DVD : distributed by Buena Vista Home Entertainment, 2002)
Collection of all 46 Schoolhouse rock! songs on the topics of science, multiplication, money, American history and English grammar. Plus, the new song "I'm gonna send your vote to college" about the American electoral college.